Prospective study of pediatric patients presenting with idiopathic infantile nystagmus—Management and molecular diagnostics - Aychoua, Nancy; Schiff, Elena; Malka, Samantha; Tailor, Vijay K; Chan, Hwei Wuen; Oluonye, Ngozi; Theodorou, Maria; Moosajee, Mariya (Frontiers in Genetics, 2022)
Idiopathic infantile nystagmus (IIN) is an inherited disorder occurring in the first 6 months of life, with no underlying retinal or neurological etiologies and is predominantly caused by mutations in the FRMD7 gene. IIN poses a diagnostic challenge, as underlying pre-symptomatic ‘multisystem’ disorders varying from benign to life-threatening should first be ruled out before nystagmus can be labelled as idiopathic. A multidisciplinary approach including, multimodal ocular investigations and next generation sequencing with whole genome sequencing (WGS) or targeted gene panel testing are required to delineate the exact etiology. We report the clinical and genetic outcomes of 22 patients, from 22 unrelated families of diverse ethnicities, with IIN seen in the ocular genetics service at Moorfields Eye Hospital NHS Foundation Trust between 2016 and 2022. Thirty-six percent (8/22) received a confirmed molecular diagnosis with eight mutations identified in 2 genes (7 in FRMD7 including one novel variant c.706_707del; p.[Lys236Alafs*66], and 1 in GPR143). This study expands the mutational spectrum of IIN and highlights the significant role of an integrated care pathway and broader panel testing in excluding underlying pathologies.